2019
DOI: 10.1186/s13287-019-1328-4
|View full text |Cite
|
Sign up to set email alerts
|

Autologous micro-fragmented adipose tissue for the treatment of diabetic foot minor amputations: a randomized controlled single-center clinical trial (MiFrAADiF)

Abstract: Background The diabetic foot ulcer (DFU) is one of the most prevalent complications of diabetes mellitus and often develops severe effects that can lead to amputation. A non-healing “minor” amputation often precedes a major amputation resulting in a negative impact on the function and quality of life of the patients. Stem cell-based therapies have emerged as a promising option to improve healing, and the adipose tissue is an abundant and easy to access source. The injection of autologous micro-fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 42 publications
2
65
0
1
Order By: Relevance
“…Studies found that SVF could secrete a variety of cytokines, differentiate into various cells such as endothelial cells, and have the potential to participate in angiogenesis in vivo. Therefore, it can improve local blood circulation and form the microenvironment that is conducive to tissue cell survival and functional maintenance [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that SVF could secrete a variety of cytokines, differentiate into various cells such as endothelial cells, and have the potential to participate in angiogenesis in vivo. Therefore, it can improve local blood circulation and form the microenvironment that is conducive to tissue cell survival and functional maintenance [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In one work (Brzezienski & Jarrell, 2016), surgeons indifferently used the GID700 and Puregraft devices, and no comparison of clinical results is made. The identified clinical results refer to multiple fields of application: 14 papers refer to breast reconstruction (Brzezienski & Jarrell, 2016;Chiu, Fracol, Feld, Qiu, & Kim, 2019;De Fazio & Cingozoglu, 2020;Economides & Song, 2018;Gabriel et al, 2017;Lee et al, 2011;Losken et al, 2011;Mestak et al, 2014;Mestak, Mestak, Bohac, Edriss, & Sukop, 2013;Mestak & Zimovjanová, 2012;Ruan et al, 2019;Russe et al, 2015;Sforza, Andjelkov, Zaccheddu, Husein, & Atkinson, 2016;Wang et al, 2012), 5 to osteoarthritis (4 of the knee and 1 of the hip) (Barfod & Blønd, 2019;Dall'Oca et al, 2019;Jones et al, 2018;Panchal, Malanga, & Sheinkop, 2018;Schiavone Panni et al, 2019), 3 to complex anal fistula (Laureti et al, 2020;Naldini, Sturiale, Fabiani, Giani, & Menconi, 2018;Topal, Eray, Rencüzo gulları, Yalav, & Alabaz, 2019), whereas 8 studies concern different pathologies (Casarotti, Chiodera, & Tremolada, 2018;Cestaro, De Rosa, Massa, Amato, & Gentile, 2015;Cherian, Malanga, Hogaboom, Pollack, & Dyson-Hudson, 2019;Hirahara, Andersen, & Panero, 2017;Kuka et al, 2020;Lonardi et al, 2019;Saibene, Pipolo, Lorusso, Portaleone, & Felisati, 2015;Zuin et al, 2019). The interesting fact is that all the aforementioned devices are mainly used for breast reconstructions, exc...…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled trial [38] the effectiveness of micro-fragmented fat tissue versus conventional treatment has been investigated in a series of patients destined for diabetic foot amputation. At 6 months, 80%, of the group treated with Lipogems MFAT healed compared to 46% of those in the group of conventional treatment.…”
Section: Plastic Surgerymentioning
confidence: 99%